PENGGUNAAN PENDEKATAN TEACHING AT RIGHT LEVEL DALAM MENANGANI PERBEDAAN TINGKAT PEMAHAMAN SISWA PADA PELAJARAN MATEMATIKA SISWA KELAS XI SMAN 12 MAKASSAR - Aisyah Aisyah; Ahmad Thalib; Muhammad Arif (Jurnal Education, 2025)
Education in Indonesia continues to progress, including in the field of mathematics education. However, mathematics is often considered a difficult subject by some students, so it can affect their learning outcomes. This research aims to improve the mathematics learning outcomes of class XI students at SMAN 12 Makassar through the application of the Teaching at the Right Level (TaRL) approach. This approach emphasizes grouping students based on their level of understanding and providing learning materials tailored to each student's needs. The research method used is Classroom Action Research (PTK) with a cycle model which includes planning, implementation, observation and reflection. The research results show that the application of TaRL has succeeded in improving students' mathematics learning outcomes. In the pre-test, only 33.33% of students achieved the Minimum Completeness Criteria (KKM), but after implementing TaRL, the percentage of learning completion increased to 66.67% in the first cycle and reached 88.89% in the second cycle. This increase was also accompanied by an increase in the average student score from 56.67 to 75. The TaRL approach, which is tailored to students' ability levels, has proven to be effective in overcoming differences in understanding between students, increasing engagement, and improving their learning outcomes. This research shows that this approach can be used as a solution to overcome gaps in understanding in mathematics learning in the classroom.